Blind third-order dispersion estimation based on fractional Fourier transformation for coherent optical communication. (1st February 2018) - Yang, Lin; Guo, Peng; Yang, Aiying; Qiao, Yaojun
Highlights: A blind third-order dispersion estimation method is proposed. Third-order dispersion can be calculated according to dispersion slope. Dispersion slope is measured based on fractional Fourier transformation. This method is robust against nonlinear and amplified spontaneous emission noise. Abstract: In this paper, we propose a blind third-order dispersion estimation method based on fractional Fourier transformation (FrFT) in optical fiber communication system. By measuring the chromatic dispersion (CD) at different wavelengths, this method can estimation dispersion slope and further calculate the third-order dispersion. The simulation results demonstrate that the estimation error is less than 2 % in 28GBaud dual polarization quadrature phase-shift keying (DP-QPSK) and 28GBaud dual polarization 16 quadrature amplitude modulation (DP-16QAM) system. Through simulations, the proposed third-order dispersion estimation method is shown to be robust against nonlinear and amplified spontaneous emission (ASE) noise. In addition, to reduce the computational complexity, searching step with coarse and fine granularity is chosen to search optimal order of FrFT. The third-order dispersion estimation method based on FrFT can be used to monitor the third-order dispersion in optical fiber system.